Laparoscopic ureteroneocystostomy: PSOAS hitch following ureteral injury during hysterectomy - Lakshmanan, Priya; Rajaraman, Sowbarnika; Durairaj, Madhumitha; Sandhiya; Poovizhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Injury to ureter is a known complication of pelvic or abdominal surgery, including laparoscopy and ureteroscopy. The incidence of iatrogenic ureteral injury during vaginal hysterectomy is 0.02 to 0.5% and after abdominal hysterectomy is 0.03 to 2%. Patient with ureteric injury should be evaluated and intervened at the earliest. The laparoscopic technique of ureteral reimplantation for the repair of ureteral obstruction due to hysterectomy injury may be challenging, but is feasible. vesicopsoas hitch is done to relieve tension after ureteroneocystostomy. A complete exposure and a good knowledge regarding the course of the ureter is necessary to avoid iatrogenic ureteral injury. JJ stenting can be done in cases with high risk of ureteric injury.